Visceral manipulation intervention in functional dyspepsia with or without gastroesophageal reflux disease: a systematic review - Achmad, Arisandy; Manaf, Haidzir (International Journal of Public Health Science (IJPHS), 2025)
Functional dyspepsia is a prevalent gastrointestinal disorder characterized by symptoms like early satiety, postprandial fullness, and epigastric pain, affecting individuals with or without gastroesophageal reflux disease (GERD). The aim was to systematically map and summarize the existing literature on visceral manipulation interventions for functional dyspepsia. The systematic review followed rigorous methodology to ensure the validity and reliability of the findings. The study involved electronic searches of four major databases and five stages to review references to screened articles from January 2012 to February 2024. The search terms include "visceral manipulation," “visceral osteopathy”, “osteopathic manipulation”, "functional dyspepsia," “gastroesophageal reflux”. Six articles were included in the review. Although there is currently little data to guide therapeutic treatment, research indicates that visceral manipulation therapy is feasible for people with functional dyspepsia, whether or not they also have GERD symptoms. Research on the effects of visceral manipulation on people with functional dyspepsia, whether or not they have GERD, is necessary to better understand treatment procedures and evaluate their advantages for patients with this condition. The growing interest in visceral manipulation intervention for functional dyspepsia is supported by mixed evidence, highlighting the need for high-quality research and larger sample sizes in future randomized controlled trials to determine its true impact.